Field application of BOFDA-based distributed fiber optic sensing in static load testing of cast-in-place pile foundations - Chen, Yue; Tian, Ze-Gang; Huang, Mao-Long; Gao, Yan-Lin; Wu, Ya-Jun; Yan, Gui-Hai (Frontiers in Built Environment, 2025)
Distributed fiber optic sensing (DFOS) offers a transformative approach for monitoring geotechnical structures by providing continuous, high-resolution strain profiles along pile shafts. In this study, a Brillouin optical frequency domain analysis (BOFDA) system was deployed to monitor seven trial cast-in-place piles subjected to vertical static load tests. Optical fibers arranged in dual U-shaped loops were embedded along the reinforcement cages, enabling detailed measurement of axial strain, load transfer, and side friction across different soil strata. Results indicate that side friction distributions captured by BOFDA generally fall below conservative site investigation values from site investigations, confirming the conservative nature of conventional design parameters. However, anomalies, such as localized overestimation of side friction in weathered sandstone, were observed in weathered sandstone layers and premature slippage near the pile head at high load levels. These behaviors highlight the sensitivity of BOFDA monitoring and the complex interplay between soil stratigraphy, pile–soil interface conditions, and applied loading. The study demonstrates that while current design practice remains safe, distributed sensing provides valuable diagnostic insights into localized side friction mobilization, supporting more refined design, improved construction quality control, and future integration of DFOS data into load-transfer modeling.